Perceptions of meaningful biology practical works in Pontianak students’ high schools - Wolly Candramila; Asriah Nurdini Mardiyyaningsih; Eria Fitriani; Khusnun Nisa Muftifah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Laboratories play a crucial role in biology education, yet inadequate facilities often hinder their optimal use. This study examines gaps in laboratory standards and analyzes student-teacher perceptions to identify improvements for practical implementation and learning outcomes. Using a descriptive qualitative survey, perceptions of laboratory use and biology practice were assessed in one public and one private high school in Pontianak, randomly selected. A 22-item closed-ended questionnaire focused on emotional experiences, procedural understanding, and comprehension of practical functions. Data were analyzed qualitatively through percentage frequencies to reveal perception patterns and challenges. Results showed significant differences between SHS A and SHS B. SHS A exhibited consistently positive perceptions across all indicators, likely due to better facilities, funding, teacher training, and supportive interactions. Conversely, SHS B displayed the less positive perceptions, particularly in emotional experiences and procedural understanding, influenced by resource limitations, insufficient guidance, and financial constraints. These findings underscore the need for adequate resources, clear instructions, and effective teacher-student engagement to enhance the quality of biology practice.